Indium-Catalyzed Direct Conversion of Lactones into Thiolactones and Selenolactones in the Presence of Elemental Sulfur and Selenium - Sakai, Norio; Horikawa, Shuhei; Ogiwara, Yohei (Synthesis, 2018)
The direct conversion of lactones into thiolactones with elemental sulfur (S8) catalyzed by InCl3/PhSiH3 in a one-pot reaction is described. This catalytic system was successfully applied to the novel preparation of selenolactones from lactones and selenium.
Keywords: thiolactone; selenolactone; lactone; indium; hydrosilane